Althusser, Marx, and a Non-empiristic Theory of History - Kužel , Petr (Dějiny – teorie – kritika, 2013)
This contribution outlines the basic principles of Althusser’s and Marx’s non-empiristic theory of history. Based on Gaston Bachelard’s historical epistemology, the author criticises methodological foundations of empiricism and a conception of science (including the historical science) that is based on it. The study presents a characterisation of Marx’s and Althusser’s theoretical principles of structural determination and pre-determination, which could be used in positively overcoming empiristic tendencies in the study of history and society.